2020
DOI: 10.21271/zjpas.32.3.11
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of infections with antibiotic-resistant Acinetobacter baumannii in different clinical samples from hospitals in Erbil

Abstract: is one of the important pathogen causing nosocomial infections. This pathogen is Acinetobacter baumannii resistant-Drug rbidity. The aim of the study becoming resistant to a large group of antimicrobial agents, leading to a high rate of mortality and mo isolates from different clinical samples and analyze its antibiotic obacter baumannii Acinet the prevalence of to determine was. During the period of study from November 2016 to December 2017, different rofiles, and pathogenic perspective susceptibility p swab,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…In the current study the main source of Acinetobacter baumannii was sputum 32 (52.46%), the second main source was blood specimens 10 (16.39%), wound swab 8 (13.11%), urine 4 (6.56%), cerebrospinal fluid (CSF) 3 (4.92%), central venous line (CV line) 2 (3.28%), and Pleural fluid 2 (3.28%) respectively were also sources for Acinetobacter baumannii. These results are consistent with finding of similar study in Erbil /Iraq, (Smai, 2020), who showed the most common isolates were detected in sputum 20 (51.3%). In contrast, other study conducted in Baghdad/Iraq, showed the most Acinetobacter baumannii isolates collected from burns (36.5%) and surgical wounds (34.1%) (Sehree et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…In the current study the main source of Acinetobacter baumannii was sputum 32 (52.46%), the second main source was blood specimens 10 (16.39%), wound swab 8 (13.11%), urine 4 (6.56%), cerebrospinal fluid (CSF) 3 (4.92%), central venous line (CV line) 2 (3.28%), and Pleural fluid 2 (3.28%) respectively were also sources for Acinetobacter baumannii. These results are consistent with finding of similar study in Erbil /Iraq, (Smai, 2020), who showed the most common isolates were detected in sputum 20 (51.3%). In contrast, other study conducted in Baghdad/Iraq, showed the most Acinetobacter baumannii isolates collected from burns (36.5%) and surgical wounds (34.1%) (Sehree et al, 2021).…”
Section: Discussionsupporting
confidence: 93%